2014
DOI: 10.3389/fgene.2014.00421
|View full text |Cite
|
Sign up to set email alerts
|

The disparity mutagenesis model predicts rescue of living things from catastrophic errors

Abstract: In animals including humans, mutation rates per generation exceed a perceived threshold, and excess mutations increase genetic load. Despite this, animals have survived without extinction. This is a perplexing problem for animal and human genetics, arising at the end of the last century, and to date still does not have a fully satisfactory explanation. Shortly after we proposed the disparity theory of evolution in 1992, the disparity mutagenesis model was proposed, which forms the basis for an explanation for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…The characteristics of this DNA’s pedigree are: 1) Genotypes which existed in the past generations can be observed in the present generation; i.e., the diversity of genotypes is enlarged accompanied by the guarantee of genotypic “principal”. 2) Even when mutation rates exceed the so-called “error threshold”, the population can be prevented from extinction because of the error-less leading strand [ 5 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristics of this DNA’s pedigree are: 1) Genotypes which existed in the past generations can be observed in the present generation; i.e., the diversity of genotypes is enlarged accompanied by the guarantee of genotypic “principal”. 2) Even when mutation rates exceed the so-called “error threshold”, the population can be prevented from extinction because of the error-less leading strand [ 5 , 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, such extreme conditions in mutation rate are not unusual for the living world. It has been reported that the mutation rate of humans and chimpanzees is 68 mutations per diploid genome per generation [6] , and that of laboratory mice 28 [7] , both of which are thought to be well over the error threshold values [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the discontinuous synthesis of the lagging strand has been postulated as a more error-prone process. This could potentially lead to an increased mutation rate that may be evolutionarily beneficial without compromising the genomic stability of the continuously synthesized leading strand (Furusawa, 2014). Additionally, it has been shown that molecular lesions created during lagging strand synthesis contribute to mating type switching in both the budding yeast S. cerevisiae and the fission yeast S. pombe (Hanson and Wolfe, 2017).…”
Section: Figurementioning
confidence: 99%
“…In keeping with this hypothesis, a recent computational analysis of human somatic variants argued that the high variance of mutation burden in adult stem cells with age supports a preferential inheritance of ancestral strands 28 . A second study from the field of evolutionary biology examined the potential influence of disparate mutagenesis of leading and lagging strand synthesis to promote variable evolutionary trajectories from the same cell population 29 . Our findings here demonstrate that, in the context of a mutator phenotype, the normal process of semi-conservative replication and Mendelian inheritance has the potential to create unequal sharing of mutations.…”
Section: Discussionmentioning
confidence: 99%